Development of Islamic Law in Indonesia: Explore Traces, Legacy and Contributions Ahmad Azhar Basyir's Thoughts - Yusdani, Yusdani; Arfaizar, Januariansyah; Asmuni, Asmuni; KS, Muslich; Arifai, Ahmad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study discusses the Islamic thoughts of Ahmad Azhar Basyir, an Indonesian scholar who has mastered Islamic sciences in various fields, and written various books on Islamic philosophy, law, jurisprudence, and economics. However, studies on the his thoughts in these various fields are rarely conducted. Today, in the renewal of Islamic legal thought and the public's enthusiasm for Islamic economics in Indonesia, it is urgent to consider and study Ahmad Azhar Basyir's thoughts. The main problem being studied is the contribution and position of his thoughts in response to the issues of nationality and community in Indonesia. The approach used in this article is a three-dimensional philosophical and socio-historical model. This study was carried out using a heuristic model, which involved stages of exploration, identification and classification of various literary sources related to Ahmad Azhar Basyir's religious thought in Indonesia. Accordingly, this study concludes with the analysis and interpretation of the various sources that have been explored, identified and classified. One of the important findings in this study is Ahmad Azhar Basyir's view regarding the renewal of Islamic thought, law and economic development which requires ijtihad, which integrates textual and contextual aspects and involves various social science and humanities disciplines. Lastly, the development of Islamic economics in various fields aims to realize the welfare of the people.